2023
DOI: 10.1186/s13018-023-03505-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of differentially expressed long non-coding RNA HOTAIR with PTEN/PI3K/AKT pathway and inflammation in patients with osteoarthritis and the effect of baicalin intervention

Abstract: Objective This study aims to investigate the correlation of long non-coding RNA HOX transcript antisense RNA (lncRNA HOTAIR) with the PTEN/PI3K/AKT pathway and clinical-related indicators in osteoarthritis (OA) and determine the effect of baicalin intervention. Methods The levels of clinical lipid metabolism indexes and immune-inflammatory indexes in OA patients and normal controls was detected. OA chondrocytes (OA-CHs) were induced with periphera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Conclusively, lncRNA HOTAIR was highly expressed in OA-chondrocytes, which facilitated OA inflammatory responses by orchestrating inflammatory cytokines and the PTEN/PI3K/AKT pathway. [ 52 ] Meng et al [ 53 ] studied the connections of markers to chondrocyte autophagy and apoptosis in OA were also comprehensively explored in vitro using molecular biology approaches. PDK1 was finally identified as a diagnostic marker for OA.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusively, lncRNA HOTAIR was highly expressed in OA-chondrocytes, which facilitated OA inflammatory responses by orchestrating inflammatory cytokines and the PTEN/PI3K/AKT pathway. [ 52 ] Meng et al [ 53 ] studied the connections of markers to chondrocyte autophagy and apoptosis in OA were also comprehensively explored in vitro using molecular biology approaches. PDK1 was finally identified as a diagnostic marker for OA.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting the expression of the lncRNA HOTAIR , decreasing the protein levels of p-PI3K and p-AKT, and increasing the protein levels of PTEN, APN, and ADIPOR1, Chen’s group discovered that baicalin plays a therapeutic role ( 72 ).…”
Section: Lncrna-related Therapymentioning
confidence: 99%
“…Flavanones , also known as dihydroflavones, lack a double bond between carbons 2 and 3, which are present in flavones and flavonols. We have found nine manuscripts regarding four molecules: baicalin, naringenin (NAR), sappanone A, wogonoside [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Baicalin is extracted from Scutellaria baicalensis Georgi, and exhibited anti-OA activities.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…In particular, lncRNA HOX transcript antisense RNA (HOTAIR) was indicated as being higher in OA chondrocytes to such an extent that it is considered a biomarker of OA in vivo. These same authors also have demonstrated that baicalin inhibits lncRNA HOTAIR expression, diminishing the protein levels of p-PI3K and p-AKT, and growing the protein levels of PTEN, OPN, and ADIPOR1 [ 43 ]. Other authors, by performing in vivo and in vitro analyses, have demonstrated that baicalin lessened OA progression in vivo and showed a chondroprotective effect in vitro by quashing chondrocyte ferroptosis, which, in turn, can reduce OA-related pain sensitivity in OA mice.…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%